2005
DOI: 10.1002/cbic.200500198
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Formation of G‐Quadruplex DNA Secondary Structures

Abstract: A little light release: Temporarily blocked (“caged”) dG nucleosides that can be incorporated into oligodeoxynucleotides are presented (see figure). Their hydrogen‐bond‐recognition site is inaccessible in the inactive form; this prevents, for example, the formation of secondary structures. Light can trigger the release of the unmodified oligonucleotide and thus induce correct folding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
1
8

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 33 publications
(25 reference statements)
0
83
1
8
Order By: Relevance
“…[33][34][35] When a photolabile 'protecting' group is attached to a biological molecule to mask its biological activity, the molecule is 'caged'. Thus, when a key thymidine or guanosine residue of the DNA antithrombin aptamer was selectively substituted with the caged analogs T NPP or dG NPP (where NPP is the photolabile 2-(2-nitrophenyl)-propyl group), the modified aptamer did not bind thrombin nor inhibit a plasma clotting assay.…”
Section: Methods To Regulate Aptamer Activity Have Been Developedmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] When a photolabile 'protecting' group is attached to a biological molecule to mask its biological activity, the molecule is 'caged'. Thus, when a key thymidine or guanosine residue of the DNA antithrombin aptamer was selectively substituted with the caged analogs T NPP or dG NPP (where NPP is the photolabile 2-(2-nitrophenyl)-propyl group), the modified aptamer did not bind thrombin nor inhibit a plasma clotting assay.…”
Section: Methods To Regulate Aptamer Activity Have Been Developedmentioning
confidence: 99%
“…Serious considerations including the sequence dependency of uncaging that may necessitate an excess of the modified aptamer, basic pH optimum (pH 11.0) for uncaging may limit the appeal of caged aptamers. 33,34 A variant of this strategy involves an aptamer-'caged' antidote chimera. 35 The chimera is a single oligonucleotide containing both an aptamer region (antithrombin DNA aptamer) and its temporarily inactivated 'caged' antisense (antidote) region (Figure 2).…”
Section: Methods To Regulate Aptamer Activity Have Been Developedmentioning
confidence: 99%
“…All other siRNA oligonucleotide single strands were chemically synthesized on an ABI 392-8 DNA synthesizer using standard phosphoramidites from AZCO. Phosphoramidites carrying an NPP group were synthesized as described before (Kröck and Heckel 2005;Mayer et al 2005). For the deprotection, oligonucleotides were treated with an 1:1 mixture of 33% MeNH 2 in H 2 O and 41% MeNH 2 in EtOH or 4 h (unmodified or caged dG) or in a 3:1 mixture of 29% NH 3 (aq.)…”
Section: Preparation and Characterization Of Oligonucleotidesmentioning
confidence: 99%
“…1B) until the photolysis event in which the caging groups are completely removed and unmodified nucleobases are formed again. In previous studies we have already shown that nucleobase-caged nucleotides can be used to trigger transcription with light, to turn protein activity either on or off, or to trigger conformational changes by using caged aptamers Kröck and Heckel 2005;Mayer et al 2005;Heckel et al 2006). Other groups used a similar approach with caged nucleobases to study RNA folding kinetics (Höbartner and Silverman 2005;Wenter et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to our initial report 3 , the site-specific caging of nucleic acids has been widely applied to regulate a variety of activities or processes including transcription, aptamer and DNAzyme activity, DNA replication and the formation of higher order RNA structures [12][13][14][15][16][17][18][19] . These experiments have involved either direct modification of pyrimidine or purine functionalities or of groups appended to them.…”
Section: Introductionmentioning
confidence: 99%